THERAPEUTIC BENEFITS OF TAKRA (BUTTERMILK) FOR HUMAN HEALTH - Anubha, *Chaudhary; Mohanlal, Jaiswal (International Journal of Ayurveda and Pharma Research, 2016)
In Ayurveda it is considered that the basis of both the health and the diseases is Ahara (food). Ahara is considered as Prana (basis of life). Acharya Kashyap had clearly stated that Ahara is the best medicine. Takra (buttermilk) is one of the Aharadravya described in Ayurved with lots of medicinal properties. Use of Takra is indicated as single drug or Anupan (vehicle) or as Pathya (wholesome) in various diseases like Grahni (sprue), piles, diarrhea etc.. Presence of MFGM, sphingolipids, casiens, lactoferrins, various vitamins etc. has been detected in buttermilk. These constituents somewhat explain the mechanism of action of buttermilk. In Bhavprakash Nighantu, it is clearly stated that a person who consumes Takra never suffers from any disease and where Takra (buttermilk) is used as medicine for a disease then there is never relapse of that disease. Takra is easily palatable and can be used both for prevention and treatment of diseases.